Consumption of Synbiotic Bread Decreases Triacylglycerol and VLDL Levels While Increasing HDL Levels in Serum from Patients with Type‐2 Diabetes. Issue 7 (6th April 2014) - Shakeri, Hossein; Hadaegh, Haleh; Abedi, Fatemeh; Tajabadi‐Ebrahimi, Maryam; Mazroii, Navid; Ghandi, Yaser; Asemi, Zatollah
Abstract: To our knowledge, no reports are available indicating the favorable effects of synbiotic bread consumption on blood lipid profiles among patients with type 2 diabetes mellitus (T2DM). This study was conducted to evaluate the effects of the daily consumption of synbiotic bread on blood lipid profiles of patients with T2DM. This randomized double‐blinded controlled clinical trial was performed with 78 diabetic patients, aged 35–70 years. After a 2‐week run‐in period, subjects were randomly assigned to consume either synbiotic ( n = 26), probiotic ( n = 26) or control bread ( n = 26) for 8 weeks. The synbiotic bread contained viable and heat‐resistant probiotic Lactobacillus sporogenes (1 × 10 8 CFU) and 0.07 g inulin (HPX) as prebiotic per 1 g. The probiotic bread contained L. sporogenes (1 × 10 8 CFU) per 1 g. Patients were asked to consume the synbiotic, probiotic and control breads three times a day in a 40 g package for a total of 120 g/day. Biochemical measurements including blood lipid profiles were conducted before and after 8 weeks of intervention. Consumption of the synbiotic bread, compared to the probiotic and control breads, led to a significant decrease in serum TAG ( P = 0.005), VLDL‐C ( P = 0.005), TC/HDL‐C ( P = 0.002) and a significant increase in serum HDL‐C levels ( P = 0.01). No significant effect of synbiotic bread consumption on FPG, TC, LDL‐C and non‐HDL‐C levels was seen compared to the probiotic and control breads ( P > 0.05). Trial registry code:http://www.irct.ir IRCT201311215623N13.